Ultra-stable narrowband green-emitting CsPbBr3 quantum dot-embedded glass ceramics for wide color gamut backlit displays. Issue 18 (21st April 2022) - Lin, Jidong; Wang, Shaoxiong; Chen, Guohua; Chen, Runyu; Chen, Shuxin; Jiang, Naizhong; Huang, Feng; Zheng, Yuanhui; Zheng, Yongping; Chen, Daqin
Abstract : A white LED backlit unit designed by coupling a CsPbBr3 @glass@PDMS green film and Mn 4+ :K2 SiF6 red film with a home-made blue light guide panel endows a liquid crystal display with a wide color gamut. Abstract : Perovskite quantum dots are considered to be one of the most promising materials for next-generation backlight displays due to their narrow emission width, high color purity and tunable luminescence. However, the deterioration and failure of perovskite quantum dots under stimulation from the external environment ( e.g., light, heat, and humid air) limit their practical applications. Herein, CsPbBr3 @glass with excellent stability and optical properties was successfully prepared by optimizing the quantum dot nucleation/growth conditions. The CsPbBr3 @glass@PDMS hierarchical structure film with a full width at half maximum of ∼17 nm and photoluminescence quantum yield of ∼80% was obtained via the physical dilution method to eliminate the internal filtering effect. Benefiting from the dual protection of the inorganic glass network and PDMS polymer matrix, the film exhibited excellent water/heat resistance. As an application demonstration, a white LED backlit unit was designed by coupling a CsPbBr3 @glass@PDMS green film and Mn 4+ :K2 SiF6 red film with a home-made blue light guide panel, endowing the LCD with a wide color gamut (a color gamut of 159% for commercial LCD, 108% for NTSC, and 81% for Rec. 2020), confirming its great potential in the display industry.